El libro de la Navidad (Autor: Carlos Alberto Rubio Torres. Editorial Universidad Nacional, Heredia, 2001) - Vargas Montero, Marco (2004)
Publicación: El libro de la Navidad (Autor: Carlos Alberto Rubio Torres. Editorial Universidad Nacional, Heredia, 2001)